PERLINDUNGAN HUKUM TERHADAP ISTRI KEDUA YANG DI POLIGAMI TANPA IZIN ISTRI PERTAMA - Nur Indah Sari (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTHusband and wife are a core part of the family where their relationship reflects how one human being with another human being of different sexes unites to form a unity to sustain life and create offspring in accordance with the ideals of the Indonesian people. But in the life of the community, it often happens that husbands who are polygamous or have more than one wife, therefore often result in neglect of child custody. But sometimes there is a husband who has polygamy or has more than one wife does not submit an application to the Court in the area where he lives. Based on